ANALISIS PENGARUH NILAI HEDONIK DAN NILAI UTILITARIAN TERHADAP KEPUASAN DAN NIAT PERILAKU PADA INDUSTRI RESTORAN - Fatikha Rizdiana Dewi (MNJ 16 UMY 296, 2016)
The purpose of this study is to analyze the effects of hedonic value and utilitarian value on satisfaction and behavioral intentions in the restaurant industry. Settings used in this research is Gubug Makan Mang Engking jalan Godean km 16 Minggir, Sleman, Yogyakarta. This research is a kind of quantitative research conducted by the survey. Data collection techniques used in this research by questionnaire. Sample of this research was consumers of Gubug Makan Mang Engking jalan Godean km 16 Minggir, Sleman, Yogyakarta and the criteria fulfilled by the researchers. The sample used in this research were 125 respondents. The sampling technique used is non probability sampling with purposive sampling method. The research is using multiple linear regression analysis. The results of this study showed the hedonic and utilitarian value has a significant and positive direct effect on satisfaction. Then the hedonic value, utilitarian value, and the satisfaction have a significant and positive direct effect on behavioral intentions. This study also showed that customer satisfaction acts as a partial mediator in the link between hedonic value and utilitarian value on behavioral intentions. Keywords: hedonic value, utilitarian value, satisfaction, and behavioral intention